DOMESTIC VIOLENCE AS A CAUSE OF DIVORCE: A LEGAL ANALYSIS OF THE SIDIKALANG RELIGIOUS COURT CONSIDERING LAW NUMBER 23 OF 2004 - Limbong, Abdul Kalam; Abd. Mukhsin, (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2024)
Domestic violence is a prevalent issue within families, often leading to divorce and posing challenges for resolution. This research investigates the factors contributing to divorce due to domestic violence in the Sidikalang Religious Court, in relation to Law Number 23 of 2004 on the Elimination of Domestic Violence. The study aims to explore the causes of domestic violence, its impact on marriages, and efforts to mitigate its occurrence. Employing a descriptive qualitative methodology, data was collected through interviews with key informants and analyzed within the framework of empirical juridical research. The findings reveal that domestic violence is defined by Law No. 23 of 2004 as any act causing physical, sexual, psychological harm, or neglect, including threats or coercion within the household. Key factors contributing to domestic violence include the husband's temperamental behavior, infidelity, arranged marriages, and external influences such as alcohol and gambling. Efforts to minimize domestic violence involve legal reforms, preventive measures, and both legal and non-legal interventions. This research provides an empirical understanding of domestic violence within the context of Indonesian law and highlights the importance of comprehensive strategies for its prevention. The originality of this study lies in its focus on case study legal research at the Sidikalang Religious Court, contributing valuable insights into the intersection of law and social phenomena. The findings underscore the need for a multi-faceted approach to address domestic violence, with implications for legal reform and policy development.